President’s Message - Farley, Margaret (Operating Room Nurses Association of Canada Journal, 2005)
Another season is approaching – spring, wonderful spring. I hope you will consider spending a portion of your spring with us at the 19th National Operating Room Nurses Association of Canada (ORNAC) Conference!